KAWASAN WISATA RIVERFRONT BERBASIS KEARIFAN LOKAL DI LOK BAINTAN - Muhammad Ikhlasul Amal; J.C Heldiansyah (ULM Press, 2021)
Lok Baintan Tourism Area is one of the plans for the development of tourist areas by the local government. Lok Baintan Village is located in Sungai Tabuk District, South Borneo. The purpose of the development of Lok Baintan Village as a tourist area is the potential of the area that has a floating market activity center as an international tourist attraction. The attraction of floating market tourism is categorized as a cultural tourism based on local wisdom considering the richness of culture in this village. But the weakness of this tourist area is the lack of tourist facilities that accommodate tourism needs. Therefore, the purpose of this design is to obtain the design of Lok Baintan Riverfront Tourist Area that accommodates tourist facilities that present cultural value and local wisdom of the region. The concept formulated is Culture Heritage Tourism based on cultural tourism that presents local values, while the method used is through Vernacular Architecture Thinking